Development to Motivate the Interest and Ability of Entrepreneurship of Medika Suherman University Students - Septia B., Rico; Nurhasan, Nurhasan (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Indonesia is a large country, but the proportion of entrepreneurs in the population is very small. Empirical facts show that the number of university graduates has increased significantly over time, while the absorption capacity of the labor market is very low. So it is deemed necessary to develop student entrepreneurship. The purpose of this activity is to provide information about entrepreneurship and increase interest in entrepreneurship for students. The PkM team helps activity participants to be motivated and have an interest in the business world through the provision of material delivered by the speakers. The PkM team also helps provide assistance and training to activity participants. Based on the PkM activities that have been carried out, it is concluded that "PkM activities add insight and knowledge related to entrepreneurship in Suherman Medika University students so that they get better and better". Of course it is important to provide entrepreneurship education so that competent young entrepreneurs develop and understand the ability and stability to progress in inculcating attitudes, behaviors, awareness and skills. This can foster an entrepreneurial spirit, attitude, behavior and skills in students and society who are competent, reliable and superior. Besides that, it will foster strong and strong entrepreneurial awareness and orientation to students and the community. Of course it is important to provide entrepreneurship education so that competent young entrepreneurs develop and understand the ability and stability to progress in inculcating attitudes, behaviors, awareness and skills. This can foster an entrepreneurial spirit, attitude, behavior and skills in students and society who are competent, reliable and superior. Besides that, it will foster strong and strong entrepreneurial awareness and orientation to students and the community. Of course it is important to provide entrepreneurship education so that competent young entrepreneurs develop and understand the ability and stability to progress in inculcating attitudes, behaviors, awareness and skills. This can foster an entrepreneurial spirit, attitude, behavior and skills in students and society who are competent, reliable and superior. Besides that, it will foster strong and strong entrepreneurial awareness and orientation to students and the community.